2013
DOI: 10.1080/03057925.2012.752622
|View full text |Cite
|
Sign up to set email alerts
|

Where should I study?: international students’ perceptions of higher education in the UK, Ireland, and the U.S.

Abstract: In the thesis I examine international student decision-making arguing that there is a gap in knowledge about the theoretical frameworks which have been applied to understanding this issue. A comprehensive review of the literature showed that thus far the foremost theory utilised for explaining international student decision-making is the Push-Pull Theory of Migration, a theory which is primarily quantitative. This research innovatively uses a theoretical framework combining three influential capital theories b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 108 publications
(441 reference statements)
0
7
0
Order By: Relevance
“…In more recent years, the Push-Pull Theory has also been used as an explanatory model for international student mobility because of its migratory nature, and pushpull factors as variables that influence students to pursue study abroad and select certain study destinations (Rounsaville, 2014). instruments were chosen because of their comprehensive attempt to expand the push-pull model.…”
Section: Measures For Study 1 (The Independent Variables)mentioning
confidence: 99%
See 2 more Smart Citations
“…In more recent years, the Push-Pull Theory has also been used as an explanatory model for international student mobility because of its migratory nature, and pushpull factors as variables that influence students to pursue study abroad and select certain study destinations (Rounsaville, 2014). instruments were chosen because of their comprehensive attempt to expand the push-pull model.…”
Section: Measures For Study 1 (The Independent Variables)mentioning
confidence: 99%
“…instruments were chosen because of their comprehensive attempt to expand the push-pull model. Each host institution also has its own set of "pull" factors which make it attractive to students, and make it more or less attractive than its competitors (Rounsaville, 2014). The literature review has shown that Mazzarol's studies are valuable to the study of the Push-Pull Theory and international student mobility.…”
Section: Measures For Study 1 (The Independent Variables)mentioning
confidence: 99%
See 1 more Smart Citation
“…Influenced by Bodycott (2009) and Rounsaville (2011), this research claims that cultural factors added, yet significant unexplored factors in determining how successful returning Nepalese graduates would be in securing employment. The results from Rounsaville (2011) had equally shown that the use of new models in analysing data could give insights into the educational decision making of international students.…”
Section: Appraisal Of Literature On Educational Decision Makingmentioning
confidence: 95%
“…Importantly their international higher education study concluded there was a requirement for researchers to pay greater attention to cultural values when looking to recruit students. Rounsaville (2011) focused on why students selected particular countries for their higher education by extending the "push-pull" models to using Human, Cultural and Social Capital. This work sought to understand the decision-making of international students using the premise that individuals invest in international education in the hope of achieving some aim or reaping some benefit.…”
Section: Appraisal Of Literature On Educational Decision Makingmentioning
confidence: 99%